Effectiveness of Ceftazidime/Avibactam treatment for infections caused by Klebsiella pneumoniae Carbapenemase (KPC), a 30-day mortality perspective. Comparison of results with control groups treated with other antibiotics - Paschke, Patrycja; Miczek, Igor; Sambura, Maria; Rosołowska-Żak, Sara; Pałuchowska, Julia; Szymkowicz, Anna (Journal of Education, Health and Sport, 2024)
Introduction: Infections caused by Klebsiella pneumoniae carbapenemase (KPC) pose a significant clinical challenge due to increasing antibiotic resistance. This study analyzes the effectiveness of ceftazidime/avibactam treatment for KPC infections, focusing on 30-day mortality and comparing results with control groups treated with different antibiotics. Material and methods: We conducted a retrospective analysis of six cohort studies, comparing thirty-day mortality in patients treated with ceftazidime/avibactam with control groups using other antibiotics. The studies included patients infected with KPC, and the analysis focused on therapeutic effectiveness. Aim of the study: The aim of the study is to compare the results in terms of 30-day mortality in groups treated with ceftazidime/avibactam compared to control groups using different antibiotics. Conclusions: Data analysis from various studies revealed varied 30-day mortality outcomes in groups treated with ceftazidime/avibactam compared to control groups using different antibiotics. Ceftazidime/avibactam proved to be more effective in all studies, reducing mortality rates compared to other treatment regimens. We emphasize that emerging antibiotic resistance, especially in the case of KPC, requires a comprehensive therapeutic approach. Despite promising ceftazidime/avibactam results, factors such as overall patient health and treatment delays may influence final therapy outcomes. We also highlight controversies regarding combination therapy vs. monotherapy, necessitating further research. Our work underscores the importance of monitoring the effectiveness of KPC infection treatment and exploring new therapeutic strategies. Further clinical studies are essential to develop a fuller understanding and optimal therapeutic protocols in the face of the growing antibiotic resistance problem.